Patient-reported outcome, clinician-reported outcome, and patient satisfaction with treatment by crisis resolution teams: a multicenter pre-post study of outcome and associated factors in Norway - T. Ruud; N. Hasselberg; J. Siqveland; K. H. Holgersen (BMC Psychiatry, 2024)
Abstract Background Crisis resolution teams (CRTs) have become a part of mental health services in many high-income countries. Many studies have investigated the impact of CRTs on acute admissions to inpatient units, but very few studies have investigated patient-reported and clinician-reported outcomes for CRT service users. Our aims were to study patient-reported and clinician-reported outcomes of CRT treatment, how the outcomes were associated with characteristics of the service user and the treatment, and whether outcomes were different across CRTs. Methods The study was a pre-post observational multicenter study of 475 patients receiving treatment from 25 CRTs in urban and rural areas in Norway. There was no control group. Outcomes were change in mental health status reported by service users using CORE-10 and by clinicians using HoNOS. Patient satisfaction was measured using CSQ-8 at the end of the treatment. Components of CRT accessibility and interventions were measured by clinicians reporting details on each session with the service user. CRT model fidelity was measured using the CORE CRT Fidelity Scale version 2. We used paired t-tests to analyze outcomes and linear mixed modeling to analyze associations of the outcomes with the characteristics of service users and the treatment provided. Using independent t-tests, we analyzed differences in outcomes and patient satisfaction between two clusters of CRTs with differences in accessibility. Results The patient-reported outcomes and the clinician-reported outcomes were significantly positive and with a large effect size. Both were significantly positively associated with practical support and medication management and negatively associated with collaboration with mental health inpatient units. Patient satisfaction was high at the end of the treatment. CRTs with higher accessibility had a significantly better clinician-reported outcome, but no significant differences were reported for patient-reported outcomes or patient satisfaction. Conclusions CRT treatment led to improved symptom status as reported by patients and clinicians, as well as high patient satisfaction. Practical support and medication management were the interventions most strongly associated with positive outcomes. Some of the variations in outcomes were at the team level. Patient- and clinician-reported outcomes should be used more in studies on the effect of treatment provided by crisis resolution teams.